Sistem Kontrol PID pada Shaking table Berdasarkan Percepatan Gempa Bumi Berbasis LABVIEW - Hariyanto, Hariyanto; Mustaghfir, Adil; Santoso, Fatih Rizqi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Earthquakes are natural disasters that can cause significant damage to buildings, necessitating an analysis of structural dynamic responses to seismic loads using a shaking table controlled by a Proportional-Integral-Derivative (PID) system based on LabVIEW. The system is designed to accurately reproduce ground motion using digital earthquake acceleration data and was tested through simulation and direct implementation with a 12 kg load. The PID tuning process employed a trial-and-error method, yielding optimal parameters of Kc = 4.5, Ti = 0.0001, and Td = 0.002. Test results demonstrated that the PID controller outperformed the Proportional (P) controller, achieving a significantly lower steady-state (0.000058 vs. 0.012745) and smaller overshoot while closely tracking the earthquake input signal. Through the integration of hardware and LabVIEW software, the system exhibited strong potential for laboratory-scale earthquake simulation and serves as a valuable tool for education and research in civil engineering and control systems